The epidemiology of hand infections and incidence of community acquired methicillin resistant staphylococcus aureus at Chris Hani Baragwanath academic hospitalri - Naidoo, Ashley (My University, 2018)
Hand Infections lead to tissue destruction, disability and financial burden. Most treatment protocols underpin Methicillin based antibiotics despite rising incidence of CA-MRSA, this study aims to assess said incidence in our community and its impact on treatment. This was a prospective cross sectional analytical study performed at Chris Hani Baragwanath Academic Hospital over a 6 month period ending 31 March 2017 of all non-surgical site hand infections. Data was collected via patient questionnaire, theatre note review and microbiology results. Our results demonstrated a predominance of Methicillin Sensitive Staphylococcus Aureus (n = 121) and an incidence of CA-MRSA of 2.5%. Our results show a statistically significant rate of repeat procedures and amputations in the CA-MRSA group especially if HIV positive (p = 0.0125). Based on the above findings we cannot recommend routine empiric Oxazolidinone therapy to cover CA-MRSA. We however wish to highlight CA-MRSA as an emerging pathogen especially in the HIV positive subgroup.
Keywords: Hand Infections; Methicillin-Resistant Staphylococcus Aureus